A relação entre conhecimentos e ação política em Francis Bacon - Branco, Daniel Artur Emidio (2013)
This dissertation aims at investigating the account of the relationship between knowledge and political action articulated by Francis Bacon (1561-1626). Special attention will be devoted to bacon’s works The Advancement of Learning (1605) and Novum Organum (1620). The methodological renewal advocated by Bacon will be situated in the context of exposition to the aristotelian legacy generated by the Renaissance Humanism and the Protestant Reformation. The use of Aristotelian terminology in Bacon’s thought will be presented as a source of confusion. In this sense, the baconian concept of form will be indicated as a clear-cut case of terminological confusion. Despite its terminological confusions and conceptual problems the method of induction proposed by Bacon fostered massive changes in scientific knowledge and signifintly influenced the life of society. In the addition to this, Bacon associated the advancement of knowledge with the idea of social progress. It may be objected that Bacon’s thought tends to subordinate ethics to technical knowledge, but there is no doubt that his contribution is essential for the understanding of the Industrial Revolution, the Enlightenment, The Positivism and the contemporary proposals of social engineering.